2006
DOI: 10.1016/j.ydbio.2006.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish cypher is important for somite formation and heart development

Abstract: Mammalian CYPHER (Oracle, KIA0613), a member of the PDZ-LIM family of proteins (Enigma/LMP-1, ENH, ZASP/Cypher, RIL, ALP, and CLP-36), has been associated with cardiac and muscular myopathies. Targeted deletion of Cypher in mice is neonatal lethal possibly caused by myopathies. To further investigate the role of cypher in development, we have cloned the zebrafish orthologue. We present here the gene, domain structure, and expression pattern of zebrafish cypher during development. Cypher was not present as a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 45 publications
3
45
0
Order By: Relevance
“…These observations were supported by morpholino knockdown of cypher in zebrafish, which also resulted in cardiac dilation and marked ventricular wall thinning, which are features associated with dilated cardiomyopathy (DCM) (Van der Meer et al 2006). Unlike in mouse, a role for Cypher in sarcomerogenesis was suggested in zebrafish studies (Van der Meer et al 2006); however, it remains to be determined if this was due to species differences or the potential redundancy of other Enigma family members at early stages of mouse somite development.…”
Section: Ablation Of Cypher In Mice Leads To Neonatal Lethalitymentioning
confidence: 96%
See 1 more Smart Citation
“…These observations were supported by morpholino knockdown of cypher in zebrafish, which also resulted in cardiac dilation and marked ventricular wall thinning, which are features associated with dilated cardiomyopathy (DCM) (Van der Meer et al 2006). Unlike in mouse, a role for Cypher in sarcomerogenesis was suggested in zebrafish studies (Van der Meer et al 2006); however, it remains to be determined if this was due to species differences or the potential redundancy of other Enigma family members at early stages of mouse somite development.…”
Section: Ablation Of Cypher In Mice Leads To Neonatal Lethalitymentioning
confidence: 96%
“…These include ZASP-1, -2, -3, -4, -5, -6, which are analogous to mouse Cypher 2s, 1s, 3s, 2c, 1c, and 3c (Vatta et al 2003). On the other hand, zebrafish cypher contains 18 exons and gives rise to at least 13 spice variants, only two of which have counterparts in mouse (Cypher 2s and Cypher 2c) (Van der Meer et al 2006). Based on the large number of splice variants identified in zebrafish, it was suggested that other splice variants of cypher may be expressed in other species (Van der Meer et al 2006).…”
Section: Identification Of Cypher Isoformsmentioning
confidence: 99%
“…For example, Cypher (also known as ZASP/oracle) (Faulkner et al, 1999;Passier et al, 2000;Zhou et al, 1999) knockout mice display severe congenital myopathy and early postnatal death, demonstrating the necessity for Z-disc integrity in contracting muscle (Zhou et al, 2001). In zebrafish, knockdown of cypher leads to severe somite and heart defects during development (van der Meer et al, 2006). MLP-null mice by contrast, display normal heart and skeletal muscle development but dilated cardiomyopathy occurs postnatally (Arber et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As its name suggests the ZASP mRNA is extensively spliced to result in multiple ZASP isoforms, a feature conserved in all species examined with four isoforms in worms [183], 12 isoforms in flies [184][185][186], 13 in zebrafish [187], and six in mice and humans [11,188] (Figure 4). In mice and humans the isoforms have been characterised according to their length and their expression in the heart or skeletal muscle.…”
Section: Zasp and Zaspopathiesmentioning
confidence: 99%